1997
DOI: 10.1507/endocrj.44.389
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Guanosine 3',5'-Cyclic Phosphate Production in Severe Pregnancy-Induced Hypertension with High Plasma Levels of Atrial and Brain Natriuretic Peptides.

Abstract: Abstract.To But in the pregnant women with severe PIH, plasma cGMP levels were significantly lower than those in pregnant women with mild PIH (P<0.05), although plasma ANP and BNP levels were higher than those in pregnant women with mild PIH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 13 publications
0
10
1
1
Order By: Relevance
“…One possible mechanism by which putative mutations in the ANP gene could exert their genetic effects is in determining presetting of ANP levels according to genotype, although plasma ANP levels are highly changeable within individuals to preserve sodium-water balance in the body. A few studies have reported distributions of plasma ANP levels in normal subjects (n l 10-36) compared with those in patients with essential hypertension [48], congestive heart failure [34] or pregnancy-induced hypertension [35]. The reported mean values in normotensive subjects (2n8-6n3 pmol\l) were not much different from our results, while concentrations were increased in diseased individuals to compensate for elevated intravascular volume overload and blood pressure.…”
Section: Discussioncontrasting
confidence: 94%
“…One possible mechanism by which putative mutations in the ANP gene could exert their genetic effects is in determining presetting of ANP levels according to genotype, although plasma ANP levels are highly changeable within individuals to preserve sodium-water balance in the body. A few studies have reported distributions of plasma ANP levels in normal subjects (n l 10-36) compared with those in patients with essential hypertension [48], congestive heart failure [34] or pregnancy-induced hypertension [35]. The reported mean values in normotensive subjects (2n8-6n3 pmol\l) were not much different from our results, while concentrations were increased in diseased individuals to compensate for elevated intravascular volume overload and blood pressure.…”
Section: Discussioncontrasting
confidence: 94%
“…Definition of normal values is needed for the use of NT‐proBNP during pregnancy. Previous studies aiming this issue had small cohorts and did not follow the subjects longitudinally (8–11). Furthermore, to our best knowledge, this is the first study comparing non‐pregnant women to pregnant women directly.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relevance of the amino acid substitution located in the prosegment of ANP to mature peptide function remains to be elucidated, a possible effect is indicated by the observation that a Gly-to-Ser substitution at position 99 (in exon 2) of the prosegment of rat ANP appears to be related to differential post-translational processing in two inbred rat strains, the stroke-prone spontaneously hypertensive rat and the Wistar Kyoto rat [47]. A few studies have reported distributions of plasma ANP levels in normal subjects (n l 10-36) compared with those in patients with essential hypertension [48], congestive heart failure [34] or pregnancy-induced hypertension [35]. This polymorphism is located within what would normally be a stop codon.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement procedures have been described elsewhere [34,35]. Briefly, peripheral blood was taken after an overnight fast.…”
Section: Measurement Of Plasma Anp Levelsmentioning
confidence: 99%